PERBAIKAN FASILITAS KERJA UNTUK MENGURANGI PEMBEBANAN OTOT STATIS PEKERJA DI BATIK SAQINA TAMIANG - Yusnawati, Yusnawati; Handayani, Nurlaila (Journal of Research and Technology, 2018)
Batik Saqina Tamiang is one of the batik craftsmen in Bandar Khalifah Village, Aceh Tamiang Regency, the batik produced is generally patterned in Aceh. The production system at Batik Saqina Tamiang is a job order and make to stock. Batik work is done manually by the workers. The results of the initial survey found complaints of static muscle loading on the body parts of the workers which caused the production lead time to be longer. This complaint arises because the worker's posture is not ergonomic when making batik. This study aims to reduce static muscle loading through the design of work facilities. The research method used in this research is descriptive, while the steps in this study are conducting field surveys and literature studies related to static muscle loading. Then do the questionnaire distribution on the bodybody map to find out the complaints felt by the workers during their work. The next step is to assess the workers' body posture using the rapid entire body assessment (REBA) method and measure the anthropometric data of the workers that will be used in the design of work facilities and then implement the work facilities that have been designed. the pain of the worker from being very ill becomes a bit painful, which occurs in the neck, shoulders and wrist.